Picture, time, movement. The cinema according to Gilles Deleuze - Ples, Marta (Folia Philosophica, 2011)
Review of Giles Deleuze's book Cinema. 1: The Movement-Image. 2: The Time-Image. Translated by J. Margański. Gdańsk: Wydawnictwo słowo/obraz/terytoria, 2008.